2006
DOI: 10.1177/1934578x0600100711
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Activity against Aedes Aegypti L. (Diptera: Culicidae) of Essential Oils of Lippia Species from Brazil

Abstract: The larvicidal activity of the essential oils from leaves of five species of Lippia (L. alba, L. aff. gracilis, L. gracilis, L. microphylla and L. nodiflora) was studied on third instar larvae of Aedes aegypti. The larvae were exposed to serial concentrations from 500 to 12.5 μg/mL of the essential oils. The results indicate that the oil of L. gracilis has a higher larvicidal activity with a LC 50 of 26.3 μg/mL The results suggest the use of these essential oils as natural larvicidal agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
1
11
3
Order By: Relevance
“…The oil extracted from the leaves of L. gracilis has been previously researched. The studies conducted by Santiago et al [ 53 ] and Silva et al [ 54 ] showed lower LC 50 values than the ones observed in this work. However, the experimental conditions were considerably different, especially compared to those utilized by Silva et al [ 54 ], who used laboratory-reared larvae.…”
Section: Resultscontrasting
confidence: 74%
“…The oil extracted from the leaves of L. gracilis has been previously researched. The studies conducted by Santiago et al [ 53 ] and Silva et al [ 54 ] showed lower LC 50 values than the ones observed in this work. However, the experimental conditions were considerably different, especially compared to those utilized by Silva et al [ 54 ], who used laboratory-reared larvae.…”
Section: Resultscontrasting
confidence: 74%
“…Plant products have been used against the vectors, and plant-derived products can act as larvicides [14]. Essential oils from plants like Lippia species [15] and Croton zehntneri [16], and various extracts and compounds [17,18] have been documented for larvicidal activity towards Aedes aegypti. As part of a continuous research program on plants from northeast Brazil, this work describes the isolation of the diterpenes zanzibaric acid and isoozic acid, and the sesquiterpene caryolane-1,9β-diol from the peel of the ripe fruits of H. courbaril, and the chemical composition of the essential oils from the peel of both ripe and unripe fruits of H. courbaril, as well as the evaluation of these oils for their larvicidal activity against A. aegypti.…”
mentioning
confidence: 99%
“…Research on the genus Lippia has been motivated in many instances by the aromatic and pharmacological properties of many of its species (for example, L. alba, L. multiflora) [1][2][3][4][5]. L. origanoides H.B.K.…”
mentioning
confidence: 99%